There is an impairment in time perception of patients with multiple sclerosis. (3rd April 2021) - Dogru-Huzmeli, Esra; Duman, Taskin
Abstract: Objective: The objective of this study is to examine time perception impairment in multiple sclerosis (MS) patients. Method: The study was performed with 60 MS patients and 60 age-matched healthy people. Estimation and Production Tests were carried out with a standard personal laptop computer and participants were aware to count the seconds by the 'start' command and to stop by the 'stop' command. The outcome measure was the ratio between the estimated duration and the target (7 s, 32 s, or 58 s) one for the Estimation Test and the Produced duration and the target (7 s, 32 s, or 58 s) one for the Production Test; and each time duration was repeated three times both for Production and Estimation Tests. Results: We found a significant difference in the Estimation Test (7 s, 32 s, 58 s), and the Production Test (7 s, 32 s, 58 s) between the MS group and healthy control group ( p < .05). It was observed that patients with MS had a higher deviation from the target time compared to the control group. It was found that this difference was statistically significant ( p < .05). There was a high and negative correlation between the Estimation and Production Tests in MS patients. Conclusion: In conclusion, our data suggests that time estimation and production are disturbed in MS patients, and cognitive rehabilitation is required for most of them.